Estrutura cristalina e molecular de complexos triazenidos n-óxidos de Cu(II), Ni(II) e Au(I) e estudo dos seus derivados imobilizados em MCM-41 - Moraes, Guilherme Alves de (2013)
Triazenes are a class of chemical compounds that presents three atoms of nitrogen bonded each other in sequence on a open chain. An analogue of these generics monocatenade Triazenes are Triazenes 1-oxide, used in many areas of chemistry, being targeted mainly in organic chemistry, analytical, medical, bioinorganic, coordination chemistry and catalysis recently. Was synthesized the free ligand 1-fenil-3-(4-Fluorophenil)Triazene N1-oxide (1) and from this, the complexes: bis[1-phenyl-3-(4-Fluorophenyl)triazene N1-oxide] Copper(II) (2), bis[1-phenyl-3-(4-Fluorophenyl)Triazene N1-oxide]Nickel(II) (3) and [1-phenyl-3-(4-Fluorophenyl)Triazene N1-oxide]-(triphenylphosphine)Gold(I) (4). The compounds were anchored on MCM-41, mesoporous molecular sieve with diameters between 2 and 50 nm , high surface area (1000 m2g-1) and high pore volume (1 cm3g-1), giving rise to solids Ligand-MCM (I), Cu-MCM (II), Ni-MCM (III) and Au-MCM (IV). The complexes and catalysts characterized by several types of analyzes such as melting point, infrared, x-ray diffraction powder and monocrystal, 1H and 13C NMR, nitrogen adsorption, TGA, among other. The solids were tested in the reactions oxidation of ciclooctene and reduction of chloro-cyclohexane to cyclohexane at different molar ratios (catalyst: oxidizing agent: substrate). This work has as main goal to discuss the crystallographic complex and present a comparison of efficiency among the catalysts supported on MCM-41.